Unraveling employee performance of hospitality sector in Surabaya: Contribution of training quality and self-efficacy - Febrinda Galuh Kirana; Dewi Khrisna Sawitri (Universitas Nusa Cendana, 2026)
This study aims to examine the effects of training quality and self-efficacy on employee performance in a five-star hotel in East Surabaya. A quantitative research design was employed using a saturated sampling technique involving 77 employees. Data were collected through a multi-source approach, with training quality and self-efficacy assessed by employees, while employee performance was evaluated by supervisors to reduce common method bias. The proposed relationships were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings indicate that both training quality and self-efficacy have positive and significant effects on employee performance. These results suggest that investments in high-quality training programs and initiatives aimed at strengthening employees' self-efficacy can effectively enhance workforce performance in the hospitality industry. This study contributes to the human resource management literature by providing empirical evidence on the complementary roles of training quality and psychological capability in improving employee performance. The findings also offer practical implications for hotel managers in designing integrated training and employee development programs to strengthen organizational performance. Keywords: Employee Performance; Hospitality; Self Efficacy; Training Quality